Role of Multidetector Computerised Tomography in the Evaluation of Pancreatic Lesions - Gupta, Kushal; Garga, UC; Gupta, Arun Kumar; Yelamanchi, Raghav; Gupta, Nikhil; Naskar, Dipankar (Nepal Medical College Journal, 2022)
The pancreas is an important exocrine and endocrine gland in the human body located in the upper abdomen. A great deal of information about the pancreas can be obtained on multi-detector computerized tomography (MDCT), including the exact location of the lesion, characterization and relation to the surrounding structures. The present study was done to evaluate the spectrum of pathologies of pancreas visualized on MDCT. A cross-sectional single center study was conducted from November 2018 to January 2020. Patients who were diagnosed with pancreatic pathology of all etiologies and satisfying the inclusion and exclusion criteria were invited to participate in the study. CT examination of the abdomen was typically performed using neutral oral contrast and non-ionic low osmolar iodinated intravenous contrast agent. Abdominal CT images were evaluated as per the standard reporting pattern and the images of pancreas were analyzed. In our study out of 33 patients, 25 patients were male and eight were female patients. Most of the patients belonged to the age group of 40-50 years. Among the various lesions diagnosed on MDCT inflammatory lesions were most common accounting for 60.6% of the cases, followed by tumors (33.3%), and congenital lesions (6.1%). MDCT is a very useful investigation to diagnose various pancreatic pathologies. Predominant pathologies diagnosed were inflammatory lesions (pancreatitis) followed by neoplasms.